Investigating the reliability and validity of the Toddler Home Learning Environment (THLE) scale - Hall, James; Sylva, Kathy; Sammons, Pamela; Smees, Rebecca; Evangelou, Maria; Smith, Teresa; Goff, Jenny (Frontiers in Education, 2021)
Home learning environments prior to school are well-known predictors of educational trajectories but research has neglected children aged under three. The new Toddler Home Learning Environment (THLE) scale is one response and this paper investigates its reliability and validity. The THLE is an adaptation of the Preschool HLE (PHLE) measure developed by the Effective Pre-School Primary and Secondary Education (EPPSE) investigation in the 1990s. The THLE was developed as part of the Evaluation of Children’s Centres in England (ECCE) investigation that followed a sample of 2,608 of families from 14 to 38 months. The THLE was administered at 14 months, the PHLE at 38. The 8-item THLE evidences internal consistency via statistical reliability coefficients and Confirmatory Factor Analysis plus measurement validity via statistically significant and research-appropriate associations with the PHLE, three measures of child development, and child and parent demographics. This paper moves the HLE literature forward with a new parental self-report scale of the HLE that is for use with toddlers.